Proyeksi Peningkatan Kebutuhan Kepala Sekolah - Mimit Sumitra; Siti Qomariyah; Muslih Muslihat; Alfian Khadafi (Journal of Creative Student Research, 2025)
At the management theory lutter gulick advanced, that budgeting is the central part of management. The program will pass premeditated when the funding is sufficient to finance the program. Including the principal's needs program. Unfortunately, though, the school principal's needs are rarely given a clear signal, and if they are realized, others like the mark up of the budget may arise. Such issues require resolution so that there is no swelling in the budgetary process, to which this inscription appears. As for the research methods used in this study are qualitative research methods, to be exact library research. With a documentary data collection technique and data analysis analysis of content analysis. His research was a projection of the principal's needs essential to the quality of education. This need has to adjust the dynamic growth of schools and policies. The main challenges include a lack of a competent headmaster, an unstandardized recruiting process, anda difficult mapping of needs in the area. Effective solutions include sustained training, instructional leadership, and stakeholder collaboration.